2015
DOI: 10.1097/cad.0000000000000184
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid A shows selective cytotoxicity against multidrug-resistant MCF-7 breast cancer cells

Abstract: Multidrug resistance (MDR) is a major cause for incurable breast cancer. Salvianolic acid A (SAA), the hydrophilic polyphenolic derivative of Salvia miltiorrhiza Bunge (Danshen/Red Sage), was examined for cytotoxicities to MDR MCF-7 human breast cancer cells and their parental counterparts. We have shown that SAA inhibited proliferation, caused cell cycle arrest at the S phase, and induced apoptosis dose dependently to the two kinds of cancer cells. However, the resistant cells were significantly susceptible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Based on these results, we conclude that transgelin 2 is vitally important for paclitaxel resistance and the migration and invasion abilities of human breast cancer cells.Recent studies have highlighted the key role of SAA in cancer therapy. For example, Wang et al31 found that SAA showed higher antitumor activity against multidrug-resistant breast cancer cells and enhanced the apoptosis of tumor cells. It was also revealed that SAA could decrease cell migration by modulating matrix metalloproteinase-9 32, 33 .…”
mentioning
confidence: 98%
“…Based on these results, we conclude that transgelin 2 is vitally important for paclitaxel resistance and the migration and invasion abilities of human breast cancer cells.Recent studies have highlighted the key role of SAA in cancer therapy. For example, Wang et al31 found that SAA showed higher antitumor activity against multidrug-resistant breast cancer cells and enhanced the apoptosis of tumor cells. It was also revealed that SAA could decrease cell migration by modulating matrix metalloproteinase-9 32, 33 .…”
mentioning
confidence: 98%
“…Salvianolic acid A (SalA) is one of the most efficacious phenolic acids of seven water-soluble compounds isolated from the Radix Salvia miltiorrhiza 11 . Many studies have reported that SalA possesses a variety of pharmacological properties, including anti-oxidant, anti-inflammatory, anti-fibrotic and anti-carcinogenic activities 12 13 14 . Moreover, SalA demonstrated potent protective effects against hepatic fibrosis in high-fat diet (HFD)-fed type 2 diabetic rats, which was likely due to its anti-oxidative and anti-apoptotic properties 15 .…”
mentioning
confidence: 99%
“…Interestingly, quercetin, which also has the same aglycone but not glycosylated, did not inhibit PRMT1. In addition, previous studies [ 46 , 47 ] reported that in vitro exposure to salvianolic acid A and naproxen decreased the expression and the efflux function of P-gp though the underling mechanism still unclear. Another study [ 48 ] reported that exposure to felodipline decrease the expression of BCRP, which is another PXR responsive gene.…”
Section: Discussionmentioning
confidence: 99%